La Modelo. De lugar de represión y cultura a lugar de cultura y participación: La Modelo. From a place of repression and culture to a place of culture and participation - Cruz Ramón, Pilar (Artigrama, 2024)
Resumen El objetivo de este artículo es analizar el papel de La Modelo de Barcelona dentro del imaginario colectivo, y su evolución desde centro penitenciario a su cierre en 2017 y posterior transformación, que prevé la conservación de parte del recinto y su reconversión en diversos usos. Se destaca el rol de La Modelo como lugar de creación cultural, incluyendo algunos episodios relevantes de su historia relacionados con la contracultura española y la cultura popular en los años 60 a 80, así como en la actualidad. Abstract The aim of this article is to analyze the role of La Modelo in Barcelona within the collective imaginary, and its evolution from penitentiary center to its closure in 2017 and subsequent transformation, which foresees the conservation of part of the space and its reconversion into various uses. The role of La Modelo as a place of cultural creation is highlighted, including some relevant episodes of its history related to the Spanish counterculture and popular culture in the 60s to 80s, as well as today. Keywords: La Modelo, prison culture, popular culture, counterculture, quinqui culture, prison heritage, creation in penitentiary centers.